Kierkegaard and Christendom - Elrod, John W. (William), 1940-2001 (Book collections on Project MUSE., 2014)
In contrast to those critics who consistently have accused Soren Kierkegaard of neglecting the social dimension of human life, John Elrod holds that in those books written after the publication of Concluding Unscientific Postscript Kierkegaard turned his attention to the social and political issues of nineteenth-century Denmark. Originally published in 1981. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions pre.